Integrating Real World Applications Into Mathematics Education: Approaches and Outcomes - Lisa Chandra Wardana; Intan Dwi Suryana; Muhamad Nandi (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This paper discusses the integration of realworld applications into mathematics education as a means to increase student interest and comprehension. It outlines various teaching strategies used to connect mathematical theories with practical problems from fields such as engineering, economics, and everyday life. The study demonstrates that students who engage with realworld applications are better able to see the relevance of mathematics in their lives and are more motivated to learn. Additionally, the research evaluates the outcomes of these integrative approaches in terms of academic performance and student attitudes.